Dampak Keberadaan Perkebunan Kelapa Sawit Pada Pembangunan Di Hulu Sungai Mahakam Kabupaten Kutai Kartanegara - Nugroho, Agung Enggal; Norhaq, Rakhmadhani (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2018)
Kutai Kartanegara Regency is one of the districts in East Kalimantan, with an area of 27,263 km2. The district is divided into three zones based on the Mahakam river flow, namely the downstream (coastal), middle and upstream zones. In the upstream area, there are many large oil palm plantation companies, which are divided into several sub-districts. However, due to its location which is quite far from the central government, and inadequate road access, some areas in the upstream zone of Kutai Kartanegara are still lagging behind in terms of development from other zones.This study aims to see the extent of the development contribution provided by the existence of oil palm plantations in the upstream zone. The intended development is seen from physical buildings and community development in the area. In addition, this study will look at community perceptions of the existence of oil palm plantations and compare whether there are differences in perceptions in each sub-district of the research location.The results showed that in general palm oil companies contributed to the provision of public facilities in the upstream area of the Mahakam River (Muara Muntai, Muara Kaman, and Kembang Janggut Subdistricts) with diverse outputs in each village. For public perceptions it is still positive both in general and specifically towards changes in the surrounding environment, and there is no significant difference in perceptions between communities in each sub-district. To optimize the role of the company in development, it certainly needs to be supported by implementing technical policies at both the central and regional levels. In addition, monitoring and evaluation from local governments in particular must be improved and sustainable. Keywords : Contributions, Oil Palm Plantation, Development